PERSONAL RESOURCES AND JOB CRAFTING: IMPLICATIONS WORK ENGAGEMENT FOR MODERN COFFE SHOPS EMPLOYEE IN MEDAN CITY - Henry Aspan; Rozaini; Etty Sri Wahyuni; Ari Prabowo (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
This research aims to determine and analyze the influence of personal resources and job crafting on work engagement of modern coffee shop employees in Medan City. The type of research used in this research is associative research with a quantitative approach. The population in this study is the population in this study, namely all lecturers at private universities in Medan City. The sampling method in this research uses a probability sampling method withsimple random sampling technique, namely taking sample members from the population randomly without paying attention to the strata in the population, with a sample size of 70 respondents in 15 modern coffee shops in Medan City. Data collection methods were carried out by means of questionnaires and interviews. The data analysis method used is multiple linear regression analysis. Based on the research results obtained partially and simultaneously, it shows that personal resources and job crafting affect the work engagement of modern coffee shop employees in Medan City. The results of the coefficient of determination test obtained an adjusted R square value of 0.863 (86.3%). This shows that the variablepersonal resourcesand job craftingable to explainwork engagementamounting to 86.3%,while the remaining 13.7% is influenced by other variables not examined inthis research.